The Effectiveness of the Flashcard-Assisted SAVI Model on Student Learning Activity in Accounting - Suci Indah Sari; Daru Wahyuni (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2026)
AbstractThe low level of student activity indicates the need to use the SAVI learning model supplemented with flashcards. The purpose of this study was to determine the effectiveness of the SAVI learning model using flashcards in increasing the activity of 11th-grade students at SMKN 1 Lemahabang. The research method used was a quasi-experimental method with a nonequivalent control group design. The sampling technique employed was purposive sampling. The analysis results show that the SAVI learning model supported by flashcards is effective in increasing the activity of 11th-grade students at SMKN 1 Lemahabang, as indicated by a higher change in the average initial and final scores in the experimental class (0.673) compared to the control class (0.251). It can be concluded that the SAVI (Somatic, Auditory, Visual, Intellectual) learning model supported by flashcards is quite effective in increasing student activity. AbstrakRendahnya tingkat keaktifan peserta didik mengindikasikan perlunya penggunaan model pembelajaran SAVI berbantuan flashcard. Tujuan penelitian ini adalah untuk mengetahui efektivitas model pembelajaran SAVI dengan menggunakan flashcard dalam meningkatkan keaktifan peserta didik kelas XI di SMKN 1 Lemahabang. Metode penelitian yang digunakan yaitu metode quasi eksperimen dengan desain nonequivalent control group design. Teknik pengambilan sampel menggunakan purposive sampling. Hasil analisis menunjukkan bahwa model pembelajaran SAVI berbantuan flashcard efektif untuk meningkatkan keaktifan peserta didik kelas XI SMKN 1 Lemahabang, ditunjukkan oleh perubahan nilai rata-rata awal dan akhir yang lebih tinggi pada kelas eksperimen (0,673) dibandingkan dengan kelas kontrol (0,251). Dapat disimpulkan bahwa model pembelajaran SAVI (Somatic, Auditory, Visual, Intelectual) berbantuan flashcard cukup efektif dalam meningkatkan keaktifan peserta didik.